(untitled) (Experimental biology, 2017)
In the rice fields Shiely district of Kyzylorda region was found 47 species and varieties of algae, including: euglenophytes - 1, green - 10 blue-green - 15, diatom - 21. Identified five bacteriological pure cultures of microalgae and cyanobacteria, and studied their morphological and cultural properties.